Synthesis and Stability of GNRA-Loop Analogs - Wörner, Karlheinz; Strube, Thorsten; Engels, Joachim W. (Helvetica chimica acta, 1999)
Nebularine, 9‐(β‐D‐ribofuranosyl)‐9H‐purin‐2‐amine, and inosine phosphoramidites 8, 16, and 17, respectively, were synthesized and incorporated into the GNRA tetraloop at different positions (see Scheme, Table, and Fig. 4). The oligomers were investigated by means of UV and CD spectroscopy to address the question of how the individual base‐modified N‐nucleosides contribute to changes in H‐bonding and base‐stacking interactions within the loop. Several CD spectra are given and compared with each other (Figs. 5 and 6). The exchange of the loop sequence in position 4 and 7 results in a distinct change in base stacking. CD‐Band shifting allows us to advance the hypothesis that a transition from a GNRA‐type towards a UNCG‐type base stacking is observed.